First Nations children from Abeenojig Dance Group in regalia - Marcia Colthorpe
Caption on verso reads: "2 girls. Native Peoples. Saddleback Family Dancers (crossed out). Abeenojig Metro Tor. Group. Dear Teacher (?). Photo property of Mariposa Folk Festival. Please Credit Marcia Colthorpe." Digitization possible through funding from Young Canada Works grant for the summer of 2018. We acknowledge the financial support of the Government of Canada. Nous reconnaissons l'appui financier du gouvernement du Canada. Screen reader support enabled.